Avaliação histopatológica da luxação extrusiva em molares de ratos - Fabre, Aubrey Fernando [UNESP] (2013)
This study evaluated the events biopathological arising from extrusive luxation in rat molars through histopathologic analysis , establishing the chronology of the repair process. One hundred and twenty male Wistar rats were used and dentoalveolar trauma (extrusive luxation) was applied to the distal surface of the maxillary right first molar. Sixty animals were extrusive luxation and sixty animals served as controls. The mesial root and distobuccal , the interradicular septum and the pulp tissue were assessed 1, 3 , 5, 7 , 14 and 28 days after the trauma by microscopic analysis of sections with three micrometers. In the groups in which animals were euthanized after 3 and 28 days the biopathological events (external root resorption, formation of hyaline areas, inflammatory infiltrate and giant cells) were more exuberant in the anatomical structures analyzed. Generally , the timing of the repair process has also been established after the luxation: early (one day post-trauma); peak of inflammation (three days); initial repair process (five days); consolidation of repair (seven days), bone formation (14 days ) and start the process of pulp necrosis (28 days).